Spanish testament / by Arthur Koestler ; with an introduction by the Duchess of Atholl - Atholl, Katharine Marjory Stewart-Murray, Duchess of (1874-1960); Koestler, Arthur (1905-1983)
En la cubierta: Left Book Club Edition